The Influence of Sustainability Reporting Disclosure, Intellectual Capital, and Good Corporate Governance on Firm Value in Telecommunication Companies Listed on The IDX in 2020-2023 - Linda Linda; Melvie Paramitha (International Journal Labs, 2025)
This study examines the effect of sustainability reporting, intellectual capital, and good corporate governance on firm value in telecommunications companies listed on the Indonesia Stock Exchange (IDX) from 2020-2023. Using quantitative approach and multiple linear regression analysis, data were collected from annual reports of 15 telecommunications companies selected through purposive sampling from a population of 22 companies. The results show that board of directors has a significant positive effect on firm value (? = 0.002), while audit committee has a significant negative effect (? = 0.037). However, sustainability reporting, intellectual capital, and institutional ownership show no significant effects on firm value (? = 0.695, ? = 0.277, and ? = 0.954 respectively). The regression model explains only 17.6% of the variation in firm value, indicating the need for enhanced transparency in sustainability reporting and intellectual capital management, as well as strengthening the role of board of directors and audit committees. These findings provide insights for management and stakeholders in formulating strategies to enhance firm value in the telecommunications sector.